(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
This paper aims at using a public call for non-objecting physicians as a springboard for a broader critical reflection on the way the topic of pregnancy termination is usually thought, that is, as a contrast between the self-determination of a pregnant woman, from a side, and the freedom of conscientious objection of the doctor, on the other. Secondly, it will illustrate how to think of the right to abortion as a mere potestative right for women is not without risks, because it could leave the pregnant woman “alone” to come to terms with her own freedom.